Mpox knowledge in the U.S.: Results from a nationally representative survey - Eric R. Walsh-Buhi; Margaret L. Walsh-Buhi; Rebecca F. Houghton (Elsevier, 2024)
Development and testing of a scale assessing mpox knowledge in a national survey of U.S. adults (aged ≥18 years) was conducted. Address-based sampling methods ensured full coverage of all households. Between September 16-22, 2022, N = 1018 participants self-administered the Internet-based survey that included a 15-item knowledge scale. Responses "yes," "no," and "I do not know," were scored as correct= 1, incorrect= −1, and "I do not know"= 0. Knowledge was dichotomized into good/poor based on modified Bloom's cutoff points (i.e. correctly answering at least 9 of the 15 total questions=good knowledge). We assessed psychometric characteristics and chi-square/one-way ANOVAs examining differences by demographic groups, applying sampling weights to analyses. Score reliability was strong (α = .82). All items but one ("Diarrhea is one of the symptoms of monkeypox") had statistically significant point biserial correlations, indicating a correlation between a correctly answered item and higher knowledge score. Only 35% of respondents were categorized as having good knowledge. Differences in knowledge by racial/ethnic, education, household income, sexual orientation, and MSA status groups were statistically significant. Mpox knowledge was lowest among heterosexually identified, rural, and low education/income respondents. Findings may be used in mpox prevention interventions, as the scale shows promise for assessing mpox knowledge in other groups/settings.